THE EFFECT OF EMOTIONAL INTELLIGENCE ON THE QUALITY OF ADMINISTRATIVE SERVICE - Agustin, Tristya Widayanti; Rahayuningsih, Idha; Fitri Sholichah, Ima (Journal Universitas Muhammadiyah Gresik Engineering, Social Science, and Health International Conference (UMGESHIC), 2021)
This study aims to examine the effect of Emotional Intelligence on the Quality of Administrative Services at the University of Muhammadiyah Gresik. Emotional intelligence is the ability of an individual to recognize himself in terms of controlling or managing emotions towards himself and others or the surrounding environment through skills of self-awareness, self-control, self-motivation, empathy, and social skills or abilities so that it can help a person achieve certain goals. according to what is expected. The higher a person's emotional intelligence, the higher his success in achieving the goals and success where he works with the resulting performance, namely by providing good service so that the quality possessed in a service also becomes good, and vice versa. In this study the method used is quantitative method with a population consisting of 101 Administrative Staff of the University of Muhammadiyah Gresik. In this case, the researcher uses incidental sampling technique. The data analysis technique used simple linear regression with a significant level of 0.05. The regression results obtained the value of r count = 0.238, then Ho was accepted and H1 was rejected. The results of the coefficient (r2) of r = 0.056 which indicates that the contribution of the emotional intelligence dimension to the quality of administrative services is 5.6%, while the rest is by other variables not examined. Based on the data analysis, it can be concluded that there is a relatively very small or no simultaneous influence of emotional intelligence on the quality of administrative services.